Populasi Serangga Hama dan Artropoda Predator pada Padi Rawa Lebak Sumatera Selatan yang Diaplikasikan Bioinsektisida dari Beauveria bassiana dan Insektisida Sintetik - Khoirul Ikhsanudin Hanif; Siti Herlinda; Chandra Irsan; Tili Karenina; Erise Anggraini; Suwandi Suwandi; Susilawati Susilawati (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2019)
Hanif et al, 2019. Population of Pest Insects and Predatory Arthropods Inhabiting Freshwater Swamp Rice of South Sumatra Treated with Bioinsectide of Beauveria bassiana and a Synthetic Insecticide. JLSO (8)1:31-38.Entomopathogenic fungi, Beauveria bassiana, could kill various species of insect pests, but their impact on predatory arthropods needs to be studied. The aim of this study was to compare population of pest insects and predatory arthropods inhabiting rice sprayed with bioinsecticide of B. bassiana and conventional rice field using a synthetic insecticides. Bioinsecticide was made from conidia of B. bassiana and sprayed on rice canopy. The plot of conventional farmers was sprayed with synthetic insecticides made from Abamektrin. The results showed that the application of bioinsecticide of B. bassiana was not proven to reduce the pest insect population. The abundance of natural enemies of pest insects, such as spiders and predatory insects was also more abundant in plots sprayed with bioinsecticide than conventional plots that used synthetic insecticide. The synthetic insecticides have been shown to reduce the abundance of predatory insects and spiders. Bioinsecticides containing carrier of liquid compost were proven to increase the growth and development of rice, which was an increase in the number of rice tillers per clump in plots applied by bioinsecticide. Thus, B. bassiana of bioinsecticide with liquid compost carrier material was safer and could maintain the abundance of predatory arthropods and increased rice growth.